Biodegradation of isoprene by soil Actinomycetota from coffee-tea integrated plantations in a tropical evergreen forest - Uttarotai, Toungporn; McGenity, Terry J.; Sutheeworapong, Sawannee; Mhuantong, Wuttichai; Khongdee, Nuttapon; Bovonsombut, Sakunnee; Chitov, Thararat (Current research in microbial sciences, 2025)
•Microbial isoprene degradation varied by plant species and season in tropical soils.•Rhodococcus and Gordonia isolates showed 50.3 % to 69.1 % isoprene degradation.•Isoprene monooxygenase genes were found in Rhodococcus and Gordonia. Isoprene, a biogenic volatile compound emitted largely by plants, can form greenhouse gases when it reacts with atmospheric radicals. A significant amount of isoprene is absorbed into soil and can be degraded by soil microorganisms, but our understanding of the microbial biodegradation of isoprene in tropical ecosystems remains limited. This study investigated isoprene degradation by soil microbes indigenous to a tropical evergreen forest, focusing on those associated with coffee and tea plants grown as integrated crops and their genome characteristics in relation to their biodegradation capabilities. Following a 96-hour incubation with 7.2 × 10⁵ parts per billion by volume (ppbv) of isoprene, soil samples exhibited degradation levels ranging from 11.95 % to 36.54 %. From these soils, bacterial isolates belonging to the genera Rhodococcus and Gordonia (Actinomycetota) were recovered. These isolates demonstrated high isoprene biodegradation activity (50.3 %–69.1 % over seven days) and carried the isoA gene associated with isoprene metabolism. According to genome analysis, the organization of genes in the iso cluster was homologous, and the encoded amino acid sequences were highly similar to those of previously known isoprene-degrading members of the same genera. These findings emphasized the contribution of these widespread isoprene-degrading bacterial genera in the biodegradation of isoprene and the role of their isoprene monooxygenases in modulating atmospheric isoprene flux. [Display omitted]